Religiosity Happiness and Helping Behavior among Female MSME Workers: Religiusitas Kebahagiaan dan Helping Behavior Pekerja Perempuan UMKM - Putri, Efriana Amelia; Rohman, Wahibur (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Prosocial behavior such as helping behavior plays a crucial role in maintaining collaboration within informal MSME work environments. Specific Background: Religiosity is associated with psychological well-being and social behavior, while happiness at work is recognized as a key psychological factor linked to prosocial actions. Knowledge Gap: Previous studies have examined religiosity, happiness, and prosocial behavior separately, with limited evidence explaining the mediating mechanism of happiness at work, particularly among female MSME workers. Aims: This study aims to analyze the relationship between religiosity and helping behavior with happiness at work as a mediating variable. Results: Using a quantitative approach with purposive sampling of 396 female MSME workers, the findings indicate that religiosity shows a positive and significant relationship with helping behavior and happiness at work, while happiness at work also shows a positive relationship with helping behavior and significantly mediates the relationship between religiosity and helping behavior. Novelty: This study develops a mediation model based on Broaden and Build Theory in the MSME context, demonstrating how religiosity contributes to prosocial behavior through positive emotional states. Implications: The findings provide theoretical support for positive psychology in informal work sectors and offer practical insights for value-based human resource management and psychological well-being strategies in MSMEs. Highlights:• Religiosity shows a direct positive relationship with prosocial workplace actions• Work happiness functions as a significant mediating mechanism• Empirical evidence derived from female workers in informal MSME settings Keywords:Religiosity; Happiness At Work; Helping Behavior; Female Workers; MSMEs